Comment pensent les chercheuses blanches ? Propositions épistémologiques et méthodologiques - Marie-Anne Paveau (Itinéraires)
This article raises the question of whiteness in research in humanities and social sciences, and more particularly in discourse analysis, at two levels: that of the object of whiteness, developed in English-speaking whiteness studies but little dealt with in France, where the field of race studies is still in its infancy; and that of the white condition of researchers working on this question, which is little questioned but nevertheless rich in epistemological and methodological issues. The article first defines the category of whiteness as a relationship of power and a relationship to knowledge and then describes the scientific and political problems it poses in research practice. Finally, it presents proposals for a research position that integrates the researcher's whiteness and develops the linguistic hypothesis of a white enunciation based on data from folk linguistics.